The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ange.201607248
|View full text |Cite
|
Sign up to set email alerts
|

A Cooperative Strategy for the Highly Selective Intermolecular Oxycarbonylation Reaction of Alkenes using a Palladium Catalyst

Abstract: Anovel method for intermolecular functionalization of terminal and internal alkenes has been designed. The electrophilic reagent, hypervalent iodine,p lays ak ey role in this process by activating the alkene C = Cbond for nucleophilic addition of the palladium catalyst. This process generates an iodonium-containing palladium species which undergoes CO insertion. The new approach, intermolecular oxycarbonylaton reactions of alkenes,h as been achieved and carried out under mild reaction conditions to produce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In stark contrast to recent reports,w ef ound that the azaoxonium ylide does not require stabilization as am etalnitrene to avoid 1,2-rearrangement to the corresponding isocyanate. [21] Bicyclic lactams (6)(7)(8)a re proposed to be the C À Hi nsertion products of the acyl nitrene.I nl ine with regular reactivity trends of nitrene CÀHi nsertions,t he most activated CÀHbond, at the ethereal methylene position, leads to the major product 6 (Scheme 4). [11,12] Minor lactam products (7,8)r esult from the other two C À Hi nsertions possible.F or several substrates,d iastereomers of lactam products are also observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast to recent reports,w ef ound that the azaoxonium ylide does not require stabilization as am etalnitrene to avoid 1,2-rearrangement to the corresponding isocyanate. [21] Bicyclic lactams (6)(7)(8)a re proposed to be the C À Hi nsertion products of the acyl nitrene.I nl ine with regular reactivity trends of nitrene CÀHi nsertions,t he most activated CÀHbond, at the ethereal methylene position, leads to the major product 6 (Scheme 4). [11,12] Minor lactam products (7,8)r esult from the other two C À Hi nsertions possible.F or several substrates,d iastereomers of lactam products are also observed.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Bicyclic lactams (6)(7)(8)a re proposed to be the C À Hi nsertion products of the acyl nitrene.I nl ine with regular reactivity trends of nitrene CÀHi nsertions,t he most activated CÀHbond, at the ethereal methylene position, leads to the major product 6 (Scheme 4). [11,12] Minor lactam products (7,8)r esult from the other two C À Hi nsertions possible.F or several substrates,d iastereomers of lactam products are also observed. Diastereomers are observed for the minor lactam products for a-substituted O-isocyanates (7d, f-j, 8d, f-j), although expectedly,n ot for the major lactam product 6d, f-j (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…[7] Herein we report the reactivity of O-isocyanates as novel uncharged 1,3-dipole equivalents,leading to reactive zwitterionic cycloadducts,a za-oxonium ylides,t hrough intra-and intermolecular oxycarbonylative alkene [3+ +2] cycloadditions. [8] To our knowledge,t he proposed aza-oxonium ylide has not been reported. [9,10] Therefore,t he subsequent reactivity of the aza-oxonium was investigated.…”
Section: Introductionmentioning
confidence: 94%
“…[21] Bicyclic lactams (6-8)a re proposed to be the C À Hi nsertion products of the acyl nitrene.I nl ine with regular reactivity trends of nitrene CÀHi nsertions,t he most activated CÀHbond, at the ethereal methylene position, leads to the major product 6 (Scheme 4). [11,12] Minor lactam products (7,8)r esult from the other two C À Hi nsertions possible.F or several substrates,d iastereomers of lactam products are also observed. Diastereomers are observed for the minor lactam products for a-substituted O-isocyanates (7d, f-j, 8d, f-j), although expectedly,n ot for the major lactam product 6d, f-j (Scheme 4).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As our ongoing research interest in the difunctionalization of alkenes, [7] we reported the first intermolecular oxycarbonylation of alkenes by using a cooperative system, where Lewis acid BF 3 •Et 2 O was required to promote I(III)mediated alkene activation, followed by a palladium-catalyzed sequential ring opening and carbonylation (Scheme 2 a). [8] However, this process could be remarkably inhibited by adding external ligands, making asymmetric oxycarbonylation extremely challenging. Alternatively, recently we found that the engineering chiral pyridinyloxazoline (Pyox) ligand by introducing a substituent into C-6 position could dramatically enhance the electrophilicity of palladium catalysts, [9] which could promote the initial enantioselective intermolecular oxypalladation.…”
mentioning
confidence: 99%